Kategoria świadka w przekładzie prozy macedońskiej / he Macedonian category of witness in Polish translations of Macedonian prose - Błaszak, Magdalena (Przekłady Literatur Słowiańskich, 2009)
The purpose of this article is to show the ways of expressing the Macedonian category of witness in Polish translations of Macedonian prose. At the beginning we present the situation of the прекажаност category against a background of the other Slavonic languages and than we characterize this category and its grammatical exponents. After that we describe the problem of truth modality which the category of witness is included in. We particularly take into concideration Polish language and the Macedonian adverbs serving this function. In the final part of this article we present some examples showing the Macedonian прекажаност category which are taken from the Polish translations of Macedonian texts. It lets us get the representation of the practical usage of the devices approchable for translators.